Ethnobotanical information on Sapium insigne (Royle) Benth.: A conserved plant of Shivalik hills, India (Bangladesh Journal of Plant Taxonomy, 2010)
Not available.Keywords: Ethnobotanical information; Latex; Shivalik hills.DOI: 10.3329/bjpt.v17i1.5396Bangladesh J. Plant Taxon. 17(1): 97-99, 2010 (June)